Revision of the genus Pseudeurybata Hennig (Diptera, Micropezidae, Taeniapterinae) - Marshall, S.a. (Zootaxa, 2016)
The previously monotypic genus Pseudeurybata Hennig is revised to include seven species from Central America and Mexico and one species from South America. Pseudeurybata rufilabris (Enderlein) and Pseudeurybata compeditus (Hennig) are given as new combinations and a lectotype is designated for P. rufilabris (Enderlein). Pseudeurybata browni and P. alces from Costa Rica, P. guatemalensis from Guatemala, P. dasypogon from Mexico, and P. zeta from Colombia and Ecuador are described as new. All species are keyed and illustrated.